Empowerment in Household Mother Group in Shredded Scallops Production of Shell in Segoro Tambak Village, Sedati Sub-district, Sidoarjo District - Diana Hertati; Nurhadi (Future Science)
Empowerment is a process that emphasizes specific strategies to empower women to become more independent. Coastal communities as farmers, processors, and traders of fish and shellfish, have complex problems. The priority problems faced by fishermen in Segoro Tambak Village in producing shredded are 1) limited knowledge and skills in shredded scallops production techniques, 2) financial management skills, and 3) limited market access for business groups (marketing). This certainly requires a third party to help improve skills in shredded scallops production techniques, financial management capabilities, and support marketing success. Based on the problems of partners, this community service activity aims to: 1) Help improve skills in shredded scallops production techniques, 2) simple bookkeeping skills for women's business groups, 3) Help overcome the problem of limited market access for business groups (marketing). The method used to help solve this problem is 1) Conducting counseling and practice of making shredded shells with the concept of high-quality and high-quality dough, 2) Simple bookkeeping training for women's business groups, 3) Counseling and practices related to selling and marketing techniques. The resulting outputs are: 1) the concept of shredded flavors with good quality, 2) the development model of the home marketing network of shredded scallops fish industry, 3) training of financial recording of small businesses using simple accounting with an individual approach carried out at the time of practice in the form of recording transactions until on the preparation of financial statements.